2010
DOI: 10.1111/j.1365-2214.2009.01000.x
|View full text |Cite
|
Sign up to set email alerts
|

How individuals with phenylketonuria experience their illness: an age‐related qualitative study

Abstract: This study constitutes a first attempt at understanding PKU from a non-medical-biological perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…Consistent with previous literature, feelings of difference to peers due to eating behavior (Zwiesele et al 2015;Vegni et al 2009), increased difficulty with dietary compliance during adolescence (Weglage et al 1992; MacLeod and Ney 2010), parental support (Shulman et al 1991), and extended family support (MacDonald et al 2010) were identified as key childhood experiences for women with PKU, shaping the perception of PKU during childhood. Consistent with Kestil€ a et al 's (2005) and Mikkil€ a et al 's (2005) findings regarding the long-term impact of early experiences, connections were noted between these childhood themes and adulthood outcomes.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with previous literature, feelings of difference to peers due to eating behavior (Zwiesele et al 2015;Vegni et al 2009), increased difficulty with dietary compliance during adolescence (Weglage et al 1992; MacLeod and Ney 2010), parental support (Shulman et al 1991), and extended family support (MacDonald et al 2010) were identified as key childhood experiences for women with PKU, shaping the perception of PKU during childhood. Consistent with Kestil€ a et al 's (2005) and Mikkil€ a et al 's (2005) findings regarding the long-term impact of early experiences, connections were noted between these childhood themes and adulthood outcomes.…”
Section: Discussionsupporting
confidence: 67%
“…Conversely, children with separated or divorced parents (Olsson et al 2007;Alaei et al 2011), an unemployed parent (Alaei et al 2011), or low socioeconomic status (Weglage et al 1992) had reduced dietary control and elevated phenylalanine (Phe) levels (MacLeod and Ney 2010). Anguish and feelings of isolation have also been found to result from awareness of the differences in eating behavior between young people with PKU and their peers (Vegni et al 2009). Adolescence can be particularly challenging.…”
mentioning
confidence: 94%
“…), worries about finding an accepting and understanding life partner or perceiving the medical condition as a limit to other relationships (Vegni et al. ; Palareti et al. ), anxiety around planning children (Dures et al.…”
Section: Resultsmentioning
confidence: 99%
“…), and the constant need to manage and tailor the consequences of the rare condition with everyday life (Vegni et al. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation